2020
DOI: 10.7759/cureus.10016
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Hepatorenal Syndrome Among Patients With Cirrhosis and Outcome After Treatment

Abstract: Introduction Hepatorenal syndrome is the third most common cause of admissions among patients with liver cirrhosis and has a high mortality rate. It is a progressive deterioration of renal function in a patient with acute or chronic liver failure. The only definite curative treatment of choice for hepatorenal syndrome is liver transplantation. This study aimed to determine the frequency of hepatorenal syndrome among patients with liver cirrhosis and to determine its outcome after treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The second most common reason for not administering corticosteroids was impaired renal function, representing 20.4% of the causes for non-eligibility. Hepato-renal syndrome has been reported to occur in approximately 10% of cirrhotic patients with ascites [27]. In our study, three-quarters of the patients were classified as having cirrhosis, with the majority in a decompensated stage.…”
Section: Discussionmentioning
confidence: 49%
“…The second most common reason for not administering corticosteroids was impaired renal function, representing 20.4% of the causes for non-eligibility. Hepato-renal syndrome has been reported to occur in approximately 10% of cirrhotic patients with ascites [27]. In our study, three-quarters of the patients were classified as having cirrhosis, with the majority in a decompensated stage.…”
Section: Discussionmentioning
confidence: 49%
“…Inayat Ullah et al [19] reported that the frequency of HRS among liver cirrhosis patients was 19.9%. Fida S et al [18] demonstrated that HRS was found in 10.3% patients who were diagnosed to have liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Duration of disease was 5.46±3.82 years in our study. A study conducted by Fida S et al [18] to evaluate the frequency of HRS among cirrhotic patients demonstrated that according to etiology 24.26% patients had hepatitis B, 30.88% patients had hepatitis C, 8.09% patients had hepatitis B and C both and remaining patients were having cirrhosis due to different etiology.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the combination-treated group to promote overall improvement in hepatic histoarchitecture underscores the therapeutic potential of the combined treatment. Prolonged liver cancer and other chronic liver injuries may lead to the development of hepatorenal syndrome characterized by renal dysfunction in patients with liver disease [33] . In the current study, the HCC model group showed notable abnormalities in the kidney, lung, and spleen.…”
Section: Discussionmentioning
confidence: 99%